A intenção subjacente aos atos de fala - Beutler, Cleonice de Oliveira Santos (2009)
This research presents a study of the intention that exists in the speech acts. The context is placed as a determinant element as far as such acts are concerned, which are units of language in use. Special attention is given to the Austinian approach for its relevance to the studies of language. The previously mentioned approach provides important contributions to the performative and pragmatic understanding of language usage. Through the speech acts theory, Austin called the attention to a new conception, where language is accepted as action, starting to be seen as nontransparent, but open to different interpretations. This conception of language is supported by the performative and pragmatic approach by Austin, Searle and Grice, beginning a new phase in the linguistic studies, a new paradigm in the language study, not only for contemporary philosophy but also for linguistics. The present work shows a different approach from the philosophers aforementioned, comparing them, in order to demonstrate that there are significant differences in relation to the way they understand the intention in the speech acts. The different understandings of these researchers are also presented as well as their definitions of locutionary, illocutionary and perlocutionary acts. Finally, the Austinian contributions to the study of language are also emphasized in the present study.